AKUNTABILITAS KEUANGAN PADA PT. ASDP INDONESIA FERRY PERSERO - Azizah, Elviana Nurul; Irma, Irmawati; Hartati, Ita (Universitas Patria Artha, 2024)
This study aims to determine the results of the effect of the implementation of Financial Accounting System and Financial Literacy on Financial Accountability at PT. ASDP Indonesia Ferry (Persero) Selayar Branch. This study used quantitative methods with descriptive research types. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. The analysis methods used are observation, questionnaires and documentation. The results show that the Financial Accounting System has a positive and significant influence on Financial Accountability. The second result shows that Financial Literacy has no effect and is significant on Financial Accountability. The third result shows that the Financial Accounting System and Financial Literacy simultaneously have a positive and significant effect on Financial Accountability.